Development of Mathematics Learning Tools of Group Investigation (GI) Model with Characters Contain to Increase Critical Thinking Ability (Journal of Primary Education, 2019)
Critical thinking helps students to study the problems systematically, face challenges with an organized, formulate innovative statements, and design original solutions. This research aims to describe the characteristics of development mathematics learning tools of GI model with scientific approaches, and examine the effectiveness of learning by using developed mathematics learning tools with scientific approach GI model's with character contain to improve critical thinking students'. This research method is R & D using 4-D models developed by Thiagarajan, Semmel & Semmel (1974) but in this research only used of three stages, namely: (a) definitions, (b) design, and (c) development. Research data obtained by observation method, documentation, questionnaire, and test. All data were analyzed descriptively, except test analyzed by statistically using validity, reliability, level of difficulty and distinguishing test. Hard work in learning is the behavior of students who show serious effort in completing tasks, focus on lessons and try to find information about lessons. The results showed that development mathematics learning tools GI model with scientific approaches integrates between indicators of competency achievement with indicators of critical thinking skills accompanied with hard work character and learning tools with scientific approaches GI models with character contained showed a significant impact in improving critical thinking student.